ANALISIS PERSEPSI SISWA PADA PROGRAM GERAKAN LITERASI SEKOLAH (GLS) DI SDN 1 TAROGONG - Hasna Nurmagfiroh; Muhammad Nurjamaludin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ perceptions of the School Literacy Movement (GLS) program at SDN 1 Tarogong. Students’ perceptions are an important factor in the success of educational programs as they influence motivation, attitudes, and student engagement. Although the GLS program has been implemented regularly, preliminary observations indicate variations in student participation, where some students show high enthusiasm while others are less engaged. This study employed a quantitative approach with a descriptive method. The sample consisted of 36 students selected randomly. The instrument used was a questionnaire based on a Likert scale covering cognitive, affective, and conative aspects. The results of the study indicate that students’ perceptions of the GLS program fall into the “good” to “very good” categories. In the cognitive aspect, students demonstrate a good understanding of the objectives and benefits of GLS in improving reading habits and knowledge. In the affective aspect, most students show positive attitudes, although some are still less interested. In the conative aspect, student participation in literacy activities is considered good, but not yet evenly distributed. These findings suggest that the success of the GLS program depends not only on its implementation but also on students’ perceptions. Therefore, it is necessary to improve the quality of the program through a wider variety of reading materials, more engaging methods, and enhanced teacher guidance to optimize students’ reading interest.